Aplikasi Teori Behavioristik dan Konstruktifistik dalam Kegiatan Pembelajaran di Sekolah Tinggi Ilmu Tarbiyah Raden Wijaya Mojokerto - Setiawan, Akhmad Pandu (Sekolah Tinggi Ilmu Tarbiyah Raden Wijaya Mojokerto, 2016)
Behaviorism learning theory is oriented towards results that can be measured and observed. Repetition and training used so that the desired behavior can become a habit. The expected results of the implementation of this behavioristic theory is the formation of a desired behavior. The desirable behavior gets positive reinforcement and behavior that is not appropriate awarded the negative. Evaluation or assessment based on observed behavior. In theory this learned professor was not much give a lecture, but the brief instruction is followed by examples by themselves or through simulation. The purpose of this paper is to describe the application of the theory Behavioristic and konstruktifistik in learning activities at the School of Raden Wijaya Tarbiyah Mojokerto. Behavioristic learning theory emphasizes the changes in behavior as well as a result of the interaction between stimulus and response. Learning is a process of behavioral changes as a result of the interaction between stimulus and response. A person is considered to have learned if he could show changes in behavior. Although learning theory tigkah behavior began to be abandoned century, but collaborate on this theory with cognitive learning theory and the theory of other learning is essential for creating a learning approach that is appropriate and effective, because basically there is no single theory of learning that is truly suited to creating a learning approaches and effective fit. especially with constructivism learning model. The role of the faculty in constructivist learning very demanding mastery of a broad and in-depth about the material taught. A broad and deep knowledge allow a lecturer accept different views and ideas of students and also makes it possible to indicate whether or not the idea of ​​the road. Mastery of the material allows a professor to understand all kinds of roads and the model to arrive at a solution to the problem without fixed on one model.